Phage-Mediated Gene Therapy - Hosseinidoust, Zeinab (Current Gene Therapy, 2017)
Background: Bacteriophages (bacterial viruses) have long been under investigation as vectors for gene therapy. Similar to other viral vectors, the phage coat proteins have evolved over millions of years to protect the viral genome from degradation post injection, offering protection for the valuable therapeutic sequence. Materials and Methods: However, what sets phage apart from other viral gene delivery vectors is their safety for human use and the relative ease by which foreign molecules can be expressed on the phage outer surface, enabling highly targeted gene delivery. The latter property also makes phage a popular choice for gene therapy target discovery through directed evolution. Although promising, phage-mediated gene therapy faces several outstanding challenges, the most notable being lower gene delivery efficiency compared to animal viruses, vector stability, and nondesirable immune stimulation. Result: This review presents a critical review of promises and challenges of employing phage as gene delivery vehicles as well as an introduction to the concept of phage-based microbiome therapy as the new frontier and perhaps the most promising application of phage-based gene therapy.
Keywords: Bionanoparticles